อัตลักษณ์ท้องถิ่นกับการจัดการท่องเที่ยวเชิงวัฒนธรรมของชุมชนมอญบ้านหนองดู่-บ้านบ่อคาว ตำบลบ้านเรือน อำเภอป่าซาง จังหวัดลำพูน: Local Identity to Cultural Tourism Management of Mon Community, Ban Nong Du and Ban Bor Kaw, Ban Ruan Subdistrict, Pasang District, Lamphum Province - ใจเป็ง, ชนิษฐา (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2024)
บทความวิชาการนี้มุ่งนำเสนออัตลักษณ์ท้องถิ่นกับการจัดการท่องเที่ยวเชิงวัฒนธรรมของชุมชนมอญบ้านหนองดู่-บ้านบ่อคาว ตำบลบ้านเรือน อำเภอป่าซาง จังหวัดลำพูน สืบเนื่องจากสังคมในปัจจุบันมีความตระหนักถึงความสำคัญของศิลปะ วัฒนธรรม เทศกาลรวมถึงมรดกทางวัฒนธรรมพื้นบ้านมากขึ้น ทั้งนี้การตื่นตัวต่อวัฒนธรรมประกอบกับความหลากหลายทางวัฒนธรรมของในแต่ละพื้นที่เป็นจุดกำเนิดของการพัฒนาแหล่งท่องเที่ยวเชิงวัฒนธรรม ดังจะเห็นว่าการท่องเที่ยงเชิงวัฒนธรรมได้กลายเป็นศูนย์กลางของอุตสาหกรรมท่องเที่ยวในอีกหลายๆ ประเทศ ซึ่งได้พยายามที่จะพัฒนาการท่องเที่ยวเชิงวัฒนธรรมในประเทศของตนเอง นอกจากการท่องเที่ยวเชิงวัฒนธรรมจะสามารถหารายได้เข้าสู่ประเทศและน่าไปสู่การพัฒนาเศรษฐกิจทั้งระดับประเทศและระดับภูมิภาคแล้วการท่องเที่ยวเชิงวัฒนธรรมยังเป็นเครื่องมือสำคัญในการสืบทอดวัฒนธรรมให้คงอยู่ต่อไป This academic article aims to present local identity and cultural tourism management of Mon Community, Ban Nong Du and Ban Bor Kaw, Ban Ruan Subdistrict, Pasang District, Lamphum Province. Due to the current society is more aware of the importance of arts, culture, festivals, and local cultural heritage. The awareness of culture together with the cultural diversity of each area is the origin of the development of cultural tourist attractions. As can be seen, cultural tourism has become the center of the tourism industry in many countries, which has tried to develop cultural tourism in their own country. In addition to cultural tourism being able to generate income for the country and leading to economic development both at the national and regional levels, cultural tourism is also an important tool for maintaining the cultural heritage